Pengajaran Konsep Ketaksamaan untuk Menguatkan Kemampuan Pemecahan Masalah Aljabar Siswa pada KSN-K Bidang Matematika di SMA Swasta Iskandar Muda Kabupaten Aceh Utara - Herizal Herizal (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service activity aimed to improve students’ ability in solving algebra’s problems in National Science Competition (KSN) in field of mathematics especially in topic of inequalities related to quadratic mean, arithmetic mean, geometrics mean, and harmonic mean. The activity was in the form of teaching concepts to three students who will participate in KSN at district level. The activity was carryout at Iskandar Muda private high school, north Aceh regency, Aceh Province. The community service method used both expository and drilling methods. Data analysis was carried out qualitatively by observing directly changes in students’ ability in solving algebraic problems given during the teaching process. The results obtained of the community service were an increase in students’ ability to apply concept of inequality related to the quadratic mean, arithmetic mean, geometrics mean, and harmonic mean in solving algebraic problems. The results can be an important thing for the students in facing KSN at the district level.